Improving the Students' Learning Activities and Mathematics Problem solving Ability in class VII Of SMP Negeri 5 Kerinci by using Think-Talk-Write Method. - Syafrizal Wandi; I Made Arnawa; Ermanto (Fakultas Ilmu Pendidikan UNP)
The ability to solve problems is one of the important goals of mathematics. In order for problem-solving ability to flourish well, the learning should actively involve students. Student learning activity class VIII SMPN 5 Kerinci is still low, resulting in the ability to solve math problems is also low. One reason is the use of learning metodees that are still focused on teachers and do not actively engage students. For that purpose, efforts are made to improve students' maturity and problem solving abilities through Think-Talk-Write learning strategy. This research is a classroom action research conducted in two cycles. The subjects of the study were students of class VIII SMPN 5 Kerinci Pelajarair Year 2015/2016 which amounted to 22 people. The results showed that the learning by using TTW learning strategy can improve the activity and problem solving ability of student math. For listening activities, paying attention to teacher explanations, asking questions, reading, understanding LKS and making important notes, interactions in discussions, and staying in groups achieve both criteria and excellent criteria for individual LKS completion activities.